Assessment of the variability of landscape components of river's mouth areas (by example of the Anankin Lake) - Tomchenko, O.V.; Khyzhniak, A.V.; Dyachenko, T. M.; Fedorovsky, O.D. (Reports of the National Academy of Sciences of Ukraine, 2018)
The possibility of estimating the variability of landscape components of river's mouth areas by the example of the Kiliya delta of the Danube — Anankin Lake, by using the multifractal analysis of remotely sensed materials is substantiated. This approach is based on the indices of variability, by using integral informative indicators of aquatic landscape complexes. It opens up new opportunities for revealing the general tendencies of changes occurring in aquatic ecosystems and can form the basis of their integrated monitoring on a qualitatively new level.